Neurobehavioral Effects of Occupational Exposure to Organic Solvents among Pharmaceutical Laboratory Workers in Iran - Aminian 1, Omid; Izadi 1, Nazanin; Esmaeili 2, Aghil; Emami 1*, Seyed Mahmoud (Shahroud Journal of Medical Sciences, 2016)
Background: Workers exposed to organic solvents are at risk of developing chronic central nervous system disorders. The aim of this cross-sectional study was to investigate the neurobehavioral effects of occupational exposure to organic solvents among pharmaceutical laboratory workers. Methods: The study groups consisted of 78 laboratory workers as the exposed group and 98 office workers as unexposed controls. The subjects were studied with the World Health Organization neurobehavioral core test battery (WHO-NCTB) by running Simple Reaction Time (SRT), Benton Visual Retention Test (BVRT) and Purdue Pegboard tests. Results: The SRT and BVRT test scores were poorer among the laboratory workers. However, no significant differences were found between the two groups for the Purdue Pegboard Test. Conclusions: The results of this study suggest that occupational exposure to organic solvents could induce a neurobehavioral deficiency in pharmaceutical laboratory workers. Therefore, objective neurobehavioral tests should be used for assessing the relation between exposure and effect and also as a guide for establishing standards in the control of workplace exposure.